Inicjacja mantrą Narasinhy i jej adoracja w tradycji pańćaratry - Dębicka-Borek, Ewa (Księgarnia Akademicka Publishing, 2019)
INITIATION WITH NARASIMHA-MANTRA AND ITS ADORATION IN PANCHARATRA TRADITION The book falls into the stream of research on the still underresearched early Vaishnava Tantric traditions. It is a valuable, detailed, and frequently meticulous philological study which focalizes on the history of literature; nevertheless, it ventures into other disciplines to look into problems underrepresented in source literature. The author begins with characterizing Hindu Tantric traditions and subsequently analyzes the initiation with the Narasimha-mantra (narasiṃhadīkṣā) followed by adoration of the mantra by aninitiated adept. The two elements are combined into “the ceremony of [the mantra] of Narasiṃha in vibhava aspect (vaibhavīyanarasiṃhakalpa).” The author grounds major tenets of her work in Sanskrit texts important for Pancharatra tradition (notably Sātvatasaṃhitā, Īśvarasaṃhitā, Narasiṃhakalpa). The overarching goal of the book is to indicate inconsistencies in how the ceremony is described in one of the oldest and most authoritative texts of Pancharatra school (circa 9th century), namely the Sātvatasaṃhitā. The author sees no logical relationship between the possibility for the initiated adept to be gifted with magic powers as a result of Narisiṃha adoration (SātS 17) and the function of a preliminary practice aimed at purification of the candidates for initiation (SātS 16). According to the author, the inconsistency may indicate re-editing of the text.